Effect of Bridging Atom and Hydroxyl Position on the Antioxidant Capacity of Six Phenolic Schiff Bases - Abdelhakim Kheniche; Imededdine Kadi; Abderrahim Benslama; Samiya Rizoug; Sarra Bekri; Abdenassar Harrar (Indonesian Journal of Chemistry, 2022)
A series of new phenolic Schiff bases N,N-bis(2,3-dihydroxybenzyl-idene)-4,4’-diphenylmethane (3-DPM), and N,N-bis(2,5-dihydroxybenzylidene)-4,4’-diphenylmethane (5-DPM), for sulfide bridge N,N-bis(2,3-dihydroxybenzyl-idene)-4,4’-diphenyl sulfide (3-DPS), N,N-bis(2,5-dihydroxybenzylidene)-4,4’-diphenyl sulfide (5-DPS), N,N-bis(2,3-dihydroxybenzyl-idene)-4,4’-diphenyl disulfide (3-DPSS), and N,N-bis(2,5-dihydroxybenzylidene)-4,4’-diphenyl disulfide (5-DPSS) were synthesized by condensation of substituted 4,4’-diamino-bis-(4-aminophenyl) methane/sulfide with various substituted aldehydes. The synthesized molecules were characterized by physical data, elemental, IR and 1H-NMR analyses. The antioxidant ability of compounds was determined through the use in vitro assays such as DPPH• scavenging, ABTS, total antioxidant capacity (TAC), hydroxyl radical OH• scavenging, and reducing power capability. The antioxidant activity of the compounds increased slightly after changing the atom bridge and hydroxyl group position. The results showed that the compound 5-DPSS exhibited superior scavenging strength against DPPH (EC50 = 7.10 ± 0.16 μg/mL), whereas 3-DPSS showed the highest activity (EC50 = 1.36 ± 0.08 μg/mL) when inspected by ABTS in relation to butylated hydroxyanisole (BHA) (EC50 = 7.54 ± 0.67). The higher OH• activity was marked by the compound 5-DPS (EC50 = 44.9 ± 3.3 μg/mL) related to BHT at (EC50 = 98.73 ± 0.3 μg/mL). The compounds 5-DPM demonstrated remarkable activity both reducing power (EC50 = 53.2 ± 0.3 μg/mL), and TAC assay (EC50 = 620.0 ± 2.4 μg/mL). These results prove that the modification in hydroxyl group position affect the antioxidant ability of Schiff bases.